2018
DOI: 10.1051/e3sconf/20184900127
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic installation for a roofed car park in Egypt as an example of effective use of solar energy

Abstract: Abstract. Photovoltaic installations are becoming an increasingly important player in the global renewable energy production market. The biggest disadvantage of photovoltaic installations is their high price, and relatively low efficiency. Photovoltaic cells achieve a theoretical efficiency of 30%, but in real conditions this efficiency is much lower at roughly 15%. Photovoltaic installations are particularly recommended in locations where the amount of solar radiation is high and where photovoltaic installati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In the hot desert climate of Cairo, it can be observed that the grid-connected PV system using a-Si [26] performs better than p-Si [27] based PV system with respectively performance ratio 77.75 % and 62%. According that the PR takes into account the overall losses of a PV system, this lower performance in the case of [27] can be attributed to the high losses in this system.…”
Section: Fig 14 Monthly Average Daily: Final Yield the Pr And The Fcmentioning
confidence: 99%
See 2 more Smart Citations
“…In the hot desert climate of Cairo, it can be observed that the grid-connected PV system using a-Si [26] performs better than p-Si [27] based PV system with respectively performance ratio 77.75 % and 62%. According that the PR takes into account the overall losses of a PV system, this lower performance in the case of [27] can be attributed to the high losses in this system.…”
Section: Fig 14 Monthly Average Daily: Final Yield the Pr And The Fcmentioning
confidence: 99%
“…In the hot desert climate of Cairo, it can be observed that the grid-connected PV system using a-Si [26] performs better than p-Si [27] based PV system with respectively performance ratio 77.75 % and 62%. According that the PR takes into account the overall losses of a PV system, this lower performance in the case of [27] can be attributed to the high losses in this system. The reported performance parameters of a 15 MWp PV power plant [4]based on amorphous silicon (a-Si) and micro-amorphous silicon (μa-Si) technologies show a final yield of 4.27 kWh/kWp and a performance ratio of 67.96 %,somewhat lower than the 4.56 kWh/kWp final yield and 77.66% performance ratio of the present study.…”
Section: Fig 14 Monthly Average Daily: Final Yield the Pr And The Fcmentioning
confidence: 99%
See 1 more Smart Citation
“…The photovoltaic parks have taken great importance as renewable energy generation systems in individual buildings integrating from the design of the building involving the architecture and installers of photovoltaic systems; thus, the photovoltaic industry is a technology that is already included in the architectural design process [8], [9] & [10].…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%